2020
DOI: 10.1101/2020.11.27.20239830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of disasters, including pandemics, on cardiometabolic outcomes across the life-course: A systematic review

Abstract: ObjectivesDisasters, such as the current COVID-19 pandemic, disrupt daily life, increase uncertainty and stress, and may increase long-term risk of adverse cardiometabolic outcomes, including heart disease, obesity and diabetes. The objective was to conduct a systematic review to determine the impact of disasters, including pandemics, on cardiometabolic outcomes across the life-course.DesignA systematic search was conducted in May 2020 using two electronic databases, EMBASE and Medline. All studies were screen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 77 publications
(286 reference statements)
0
7
0
Order By: Relevance
“… 8 , 10 Previous research on population-level disasters, including earthquakes and floods, has found that exposure to stress during an acute disaster has a profound impact on long-term health outcomes, including chronic diseases. 11 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 10 Previous research on population-level disasters, including earthquakes and floods, has found that exposure to stress during an acute disaster has a profound impact on long-term health outcomes, including chronic diseases. 11 …”
mentioning
confidence: 99%
“…8,10 Previous research on population-level disasters, including earthquakes and floods, has found that exposure to stress during an acute disaster has a profound impact on longterm health outcomes, including chronic diseases. 11 Given the dramatic change in daily functioning during the COVID-19 pandemic, several factors (e.g., limited access to physical activity facilities, closures) may contribute to increased incidence of obesity, cardiovascular disease and type 2 diabetes; however, it has been hypothesized that chronic stress, in particular, may influence disease development. 12…”
mentioning
confidence: 99%
“…6 Most literature on climate change-related exposures and health focuses on acute or short-term effects. 7,8 Incorporating an LCE approach into climate and health research would expand this literature to understand the latent effects of early-life exposures over the entire life course. An LCE-CEHH approach will focus attention on the acute health effects of climate change-related exposures that occur at all ages, as well as the delayed effects of single or cumulative climate exposures.…”
Section: A Life Course Epidemiology Approach To Climate Extremes and ...mentioning
confidence: 99%
“…The extent to which these behaviors further promote increased rates of noncommunicable diseases, especially cardiometabolic diseases, and their associated mortality as well as psychiatric manifestations, even after the pandemic, cannot yet be determined. Drawing on analyses of previous disasters and pandemics, De Rubeis et al [7] and Muehlschlegel et al [8] have suggested that they may lead to behavioral changes, such as negative changes in physical activity, sleep, and diet, as well as increased alcohol consumption and intoxication as a consequence of stress exposure and lack of access to health services (among other factors), thus contributing to an increased incidence of noncommunicable diseases over the life course. So far, research focused on the consequences of voluntary self-quarantine or stay-at-home policies, not on infected persons (IP) or their close contact persons (CP), who were legally enforced into quarantine by local public health departments.…”
Section: Introductionmentioning
confidence: 99%